MODUS OPERANDI DAN PENEGAKAN HUKUM MAFIA TANAH - Fathullah, Kholidazia El Hamzah (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstrack Modus Operandi And Law Enforcement Of The Land Mafia (Case Study in Wonokerto Village, Tekung District, Lumajang Regency)" aims: 1) To examine and analyze the modus operandi of the land mafia in Wonokerto Village, Kec. Tekung Regency Lumajang; 2) To analyze land mafia law enforcement in Wonokerto Village, Kec. Tekung Regency Lumajang. This research uses empirical legal research with a juridical-sociological approach which is research based on applicable statutory provisions associated with legal theory and looks at the reality that occurs in society, namely related to the modus operandi of the land mafia and how the law is enforced in Wonokerto Village, Kec. . Tekung Regency Lumajang. Keywords: Modus Operandi, Law Enforcement, Land Mafia